Mechanical anisotropy and tabletability of famotidine polymorphs. Issue 9 (15th February 2022) - Upadhyay, Pratik P.; Mishra, Manish Kumar; Ramamurty, Upadrasta; Bond, Andrew D.
Abstract : Nanoindentation studies on two polymorphs of famotidine indicate that the degree of anisotropy of their elastic response is an important indicator of their comparative tabletability. Abstract : In the drug development process, early characterization of solid forms can help to envisage the bulk processability of a powder, which should assist in selecting an optimal solid form. In this context, we examine the mechanical properties of two polymorphs of famotidine, form A and form B, using nanoindentation on multiple faces of single crystals to assess the degree of anisotropy. Crystals of form A obtained from acetonitrile typically present two different faces suitable for indentation. For form B, crystallization from ethanol yields two different crystal habits, which together allow for indentation on two crystal faces. On the basis of the two faces examined for each polymorph, form B shows a highly anisotropic elastic modulus ( E ), but an approximately isotropic hardness ( H ), while form A shows approximately isotropic values for both E and H . Hydrogen-bonding patterns and energy-vector models indicate a 3-D nature for the crystal structure of form A, but an apparent 2-D nature for form B, which is qualitatively consistent with the observed difference in anisotropy. The structure of form B contains regions expected to act as slip planes but the similarity between the H values obtained for forms A and B indicates that these do not impart significant plasticity, apparently due to a corrugated topology. For sieved powder samples with particle size less than 125 μm, form A displays better tabletability than form B, especially at higher applied pressures. The overall isotropic nature of the mechanical properties in form A, compared to the highly anisotropic elastic response of form B, appears to be an important indicator of the comparative tabletability of these two polymorphs.